Equilibrium properties and decoherence of an open harmonic oscillator. (19th May 2020) - Polonyi, Janos
Abstract: The equilibrium properties of an open harmonic oscillator are considered in three steps: first the creation and destruction operators are generalized for open dynamics and the creation operator is used to construct coherent states. The second step consists of the introduction of the Heisenberg representation where the dynamical decoherence is identified. Finally it is pointed out that the quantum fluctuations generate non-continuous limit for infinitesimal system–environment interactions and at the border of the under- and over-damped oscillator.